PERANAN KELOMPOK TANI â€œTENGGANG RASAâ€ TERHADAP PENGEMBANGAN TANAMAN KAKAO DI DESA INOMUNGA, KECAMATAN KAIDIPANG, KABUPATEN BOLAANG MONGONDOW UTARA - Margaretha ., Impal; Benu Olfie L. S.; Vicky R. B. Moniaga (AGRI-SOSIOEKONOMI, 2017)
This study aims to describe the role of Farmers Group "Tenggang Rasa" to the development of cocoa plants in the village of Inomunga, Kaidipang Sub-district, Utara Bolaang Mongondow District, North Sulawesi Province. The study lasted for 3 (three) months from January to March 2017 in Inomunga Village, Kaidipang Sub-district, Bolaang Mongondow Utara District. The data used were primary data collected through interviews with all members of farmer group "Tenggang Rasa" which amounted to 15 people as respondents. Secondary data were obtained from the Agricultural Office, the Inomunga Village Office and the District Office in Bolaang Mongondow Utara. The analytical method used is descriptive through Likert Scale and presented in tabular form. The results showed that â€œTenggang Rasaâ€ Farmer Group in Inomunga Village has a very important role as learning class, cooperation vehicle and production unit to develop cocoa plant by getting index of role which belong to high category that is 82,85 percent. With the existence of farmer groups, farmers are very helpful in overcoming their problems to get solution for the development of cocoa plants.